Changes in innate and adaptive immunity during human ageing 2 - De Maeyer, Roel (Henry Stewart Talks, 2022)
Low-grade, chronic systemic inflammation: inflammageing, p38 drives inflammageing, Senescence-associated secretory phenotype (SASP) inflammageing, Blocking inflammageing: ARISE, Implications for COVID